2021
DOI: 10.1002/cctc.202100054
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Imaging of Mixed Metal Oxide Catalysts for Propylene Oxidation: From Model Binary Systems to Complex Multicomponent Systems

Abstract: Industrially-applied mixed metal oxide catalysts often possess an ensemble of structural components with complementary functions. Characterisation of these hierarchical systems is challenging, particularly moving from binary to quaternary systems. Here a quaternary BiÀ MoÀ CoÀ Fe oxide catalyst showing significantly greater activity than binary BiÀ Mo oxides for selective propylene oxidation to acrolein was studied with chemical imaging techniques from the microscale to nanoscale. Conventional techniques like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Tomographic techniques allow such a 3D visualization and additionally provide the possibility of unravelling individual catalyst phases present, whose features typically overlap during integral characterization by XRD, XAS or Raman spectroscopy for example. The emerging chemical imaging techniques (i. e. hard X-ray tomography) have already been proven to be a valuable tool for unravelling structural changes of Bi-Mo-Co-Fe-oxides [38][39] and other multi-component catalyst systems under in situ or operando conditions. [40][41] Sprenger et al observed by 3D X-ray nanotomography studies on spent Bi-Mo-Co-Fe-O particles a heterogeneous metal oxide phase distribution [38] and elemental distribution with a strong bismuth aggregation [39] within the whole catalyst volume (Figure 4).…”
Section: Towards Multicomponent Systems: the Need Of (Advanced) Compl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tomographic techniques allow such a 3D visualization and additionally provide the possibility of unravelling individual catalyst phases present, whose features typically overlap during integral characterization by XRD, XAS or Raman spectroscopy for example. The emerging chemical imaging techniques (i. e. hard X-ray tomography) have already been proven to be a valuable tool for unravelling structural changes of Bi-Mo-Co-Fe-oxides [38][39] and other multi-component catalyst systems under in situ or operando conditions. [40][41] Sprenger et al observed by 3D X-ray nanotomography studies on spent Bi-Mo-Co-Fe-O particles a heterogeneous metal oxide phase distribution [38] and elemental distribution with a strong bismuth aggregation [39] within the whole catalyst volume (Figure 4).…”
Section: Towards Multicomponent Systems: the Need Of (Advanced) Compl...mentioning
confidence: 99%
“…The emerging chemical imaging techniques (i. e. hard X-ray tomography) have already been proven to be a valuable tool for unravelling structural changes of Bi-Mo-Co-Fe-oxides [38][39] and other multi-component catalyst systems under in situ or operando conditions. [40][41] Sprenger et al observed by 3D X-ray nanotomography studies on spent Bi-Mo-Co-Fe-O particles a heterogeneous metal oxide phase distribution [38] and elemental distribution with a strong bismuth aggregation [39] within the whole catalyst volume (Figure 4). This bismuth segregation from the catalyst surface was in good agreement with XPS, XAS and TEM-EDX results and further indicates that the previously proposed core-shell like particle model with a bismuth molybdate rich surface cannot generally be applied to describe such complex catalyst systems.…”
Section: Towards Multicomponent Systems: the Need Of (Advanced) Compl...mentioning
confidence: 99%
“…33 At the same time, Molybdenum bismuth catalysts have been widely concerned in the field of oxidative dehydrogenation owing to their redox properties. [34][35][36][37] They have good stability and catalytic activity in the oxidation, and more importantly, some observation indicated that their catalytic performances could be changed along with altering the pH value in the prepared procedure. 38,39 Although great efforts had been devoted to the development of effective progress for the production of DFF from bio-based furan derivatives, most of these approaches suffer from one or more shortcomings, such as low yield, tedious work-up processes, difficulty in reusability of the catalyst, and poor selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…could bring out DFF with 99% yield in p ‐chlorotoluene 33 . At the same time, Molybdenum bismuth catalysts have been widely concerned in the field of oxidative dehydrogenation owing to their redox properties 34‐37 . They have good stability and catalytic activity in the oxidation, and more importantly, some observation indicated that their catalytic performances could be changed along with altering the pH value in the prepared procedure 38,39 …”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction computed tomography (XRD-CT) is a powerful characterisation technique which has been lately applied to study a variety of functional materials and devices including operating solid catalysts, fuel cells and batteries. [53][54][55][56][57][58][59][60][61][62][63][64] The radial distribution of the various crystalline catalyst components under operating conditions was investigated with the 3D-XRD-CT technique. In addition, the fast solidstate changes occurring along the catalyst bed were followed with X-ray diffraction mapping.…”
Section: Introductionmentioning
confidence: 99%